Education Evaluation – A Proposed Approach for the Technical Schools in Romania. (2015) - Baesu, Viorica; Marian, Liviu; Farkas, Zoltan-Bela; Draghici, Anca
Abstract: The article presents a research approach and results on how education evaluation through teachers' motivation (intrinsic and extrinsic factors), collective efficacy perception, and how they can affect professional satisfaction and forward teaching staff performance. The propose approach methodology is based on a designed questionnaire. In addition, the evaluation approach was applied in the case of the technical education system in Romania, West Region. The research results and conclusions are expected to play an important role for improving teaching processes quality for better development of technical competencies in secondary schools. The statistical data process considered the research hypothesis gives the research results and support the empirical model related to evaluation of the complex motivation – satisfaction – performance interdependences.